OPTIMAL INVESTMENT PORTFOLIO SELECTION BASED ON SECTOR ROTATION STRATEGY - William Kinsey, Grandy
The Indonesia economic growth has been getting better over the years motivates both domestic and foreign investors to invest their funds. One of the best return investment instruments in Indonesia is equity fund. The objective of this investment is to achieve the best return through capital gains and dividends.